Spatial Analysis of Determinants of Hypertension Incidence in Kota Lama Subdistrict, Kupang, Indonesia - Dominggus Agustinus Isak Lenda; Pius Weraman; Yendris Krisno Syamruth; Apris A Adu; Anderias Umbu Roga (Journal of Epidemiology and Public Health, 2025)
Background: Cardiovascular diseases such as hypertension, heart attack, and stroke are chronic non-communicable diseases influenced by genetic, physiological, environmental, and behavioral factors. Geographic Information Systems (GIS) can be utilized for spatial analysis to identify risk factors, distribution patterns, and determinants of diseases, including hypertension. This study aims to examine the determinants of hypertension using a spatial analysis approach in Kota Lama Subdistrict, Kupang City.Subjects and Method: This study employed an ecological study design using an observational analytic method with a cross-sectional approach. The population consisted of residents aged ≥18 years in Kota Lama Subdistrict. A total of 400 individuals diagnosed with hypertension were selected using simple random sampling. The variables examined were age, overweight, lack of physical activity, high-salt diet, alcohol consumption, medication adherence, economic level, and distance to health facilities. Instruments used included a sphygmomanometer, microtoise, weight scale, and questionnaire. Spatial analysis was conducted using the GeoDa application with Regression, Bivariate Local Moran’s Index, Multivariate Local Geary, and Spatial Empirical Bayes tests.Results: The results showed significant associations and clustered spatial autocorrelation with low-to-high relative risk (RR) observed in the subdistricts of LLBK, Bonipoi, Solor, Fatubesi, Oeba, Nefonaek, and Pasir Panjang for the variables: age (p=0.001, I=0.70), overweight (p<0.001, I=0.64), lack of physical activity (p=0.00, I=0.63), high-salt diet (p=0.00, I=0.63), and alcohol consumption (p<0.001, I=0.69). There were no significant associations for variables such as irregular medication intake, economic level, and distance to health facilities, with p-values of 1.000 > α (0.050).Conclusion: Age, overweight, physical inactivity, high-salt diet, and alcohol consumption are significant determinants and show positive clustered spatial autocorrelation with hypertension. It is recommended that individuals over 40 years of age regularly monitor their blood pressure, maintain a healthy diet, engage in sufficient physical activity, and for those with hypertension, adhere to regular medication intake.